Geophysical method exploration for slope failure investigation - N. H., Abdullah; I. B., Mohamed Jais; Haryati, Awang (IOP Publishing, 2020)
A combination of seismic refraction survey, electrical resistivity method and integration with borehole method has been used for ground exploration to study the slope surface failure along the study area at Kayangan Height, Selangor. This study focuses on investigating the possible cause of the slope failure at the area. By necessity, non-destructive method like electrical resistivity test is the most suitable method as this method can determine the subsurface water conditions. Meanwhile, seismic refraction test is able to determine the type of subsurface layers and level of bedrock. Seismic refraction test can guide the borehole drilling works which can provide borelog data. Based on the study, seismic tomogram and 2D resistivity imaging results provide complementary information to each other. The existing geotechnical borehole logs refined both seismic and 2D resistivity results. Therefore, the study shows that the electrical resistivity test, seismic refraction test and borelog data in combination, could be an effective tool and cost effective for slope failure investigation.